1995
DOI: 10.1002/env.3170060203
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of asbestos fibre counts

Abstract: SUMMARYWe present methods for estimating asbestos fibre concentrations based on the negative binomial distribution for fibre counts. This distribution is preferred to the usual Poisson due to the extra variability encountered in the data. We extend the method to incbde estimation of the parameters of a log-normal population of concentrations, and deal with the problem of zero counts. We illustrate the methods on a set of 921 fibre counts from 177 school buildings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Since all but one of the samples reported values lower than the limits of detection, it was necessary to assume some Wnite number Table 1 Engine disassembly tasks * Asbestos-containing gasket (see Table 2). (a) that sample concentrations were at the limit of detection for each sample, (b) that sample concentrations were one-half of the detection limit for each sample (Oehlert et al, 1995).…”
Section: Time Weighted Average Exposuresmentioning
confidence: 99%
“…Since all but one of the samples reported values lower than the limits of detection, it was necessary to assume some Wnite number Table 1 Engine disassembly tasks * Asbestos-containing gasket (see Table 2). (a) that sample concentrations were at the limit of detection for each sample, (b) that sample concentrations were one-half of the detection limit for each sample (Oehlert et al, 1995).…”
Section: Time Weighted Average Exposuresmentioning
confidence: 99%
“…Some investigators [50,86] have suggested that one half of the detection limit value should be used for statistical calculations. Use of the detection limit value provides the highest numerical exposure and may be more applicable for some studies as a method of incorporating a safety factor and in determining exposure and hazard assessment criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators [81,82] have suggested that one half of the detection limit value should be used for statistical calculations. Others have suggested using values at the numerical number reported [73,83].…”
Section: Methodsmentioning
confidence: 99%